ENTIDADES DE EDUCAÇÃO PROFISSIONAL: A IMPORTÂNCIA DOS SEUS ASPECTOS DE GESTÃO PARA A REDUÇÃO DOS ÍNDICES DE DESEMPREGO NO BRASIL - Mathias, Sérgio Machado (2006)
This dissertation objectifies to analyze one of the most important factors for the employability nowadays: the professional education. More than this, it was intended to demonstrate that this professional education, exerted of competent form for the profferer entities, can be changed into one of the solutions for the resolution of one of the most serious social problems of the Country: the unemployment. The dissertation is the result of the exploratory and bibliographical research, which had for objective the identification of factors that influence the occurrence of the studied phenomena, in order to provide the possibility of the deepening of the reality, searching to explain its reasons and the justifications of its reasons. Although being one of the proposals of the effective legal mechanisms, the professional education still did not become an instrument capable to increase the level of schooling of the worker and for force of this it does not keep faithful tuning with the chances offered for the work market, each more selective and demanding time. However, the professional education if affirms as one of the important factors of employability in the State of Rio de Janeiro, collaborating significantly in the reduction of the local indices of unemployment.